Peranan Ultrasonografi Toraks dalam Menegakkan Diagnosis Beberapa Kelainan pada Paru: [The Role of Ultrasound in Diagnosing Pulmonary Diseases] - Winaya, Erwin; Koesoemoprodjo, Winariani (Jurnal Respirasi, 2015)
Ultrasound is useful in the diagnosis of cases in the field of lung disease, such as pleural effusion, pneumothorax, consolidation, atelectasis, pulmonary edema, and others. The advantages of thoracic ultrasound is a low cost, radiation is small, easy to carry, short examination time and has a dynamic aspect that can be seen at the time of examination. Thoracic ultrasound is an inexpensive tool and can be used to assist in intervention, especially in cases of peripheral lung, pleura and chest wall diseases, such as thoracocentesis, chest tube installation and aspiration lung abscess. Ultrasound can also replace aspiration and biopsy with CT-scan guidance in cases involving the pleura, chest wall, and lung tumors that invade the pleura and chest wall. With the ultrasound portable and compact form, in the future is possible if the ultrasound will be a routine part of the examination as well as a stethoscope. However, ultrasound also has limitations which in patients with subcutaneous emphysema, peripheral edema and obesity, lung ultrasound is hard to do. Ultrasound examination is also highly dependent on the experience and ability of the ultrasound operator.